Effect of Die Spacer Thickness on the Microshear Bond Strength of CAD/CAM Lithium Disilicate Veneers - Sherine Mohamed Farag; Mona Mohamed Ghoneim; Rania Reda Afifi (International Journal of Dentistry)
Aim. The aim of this study was to compare the microshear bond strength of ceramic veneers with digital die spacer settings at 20, 40, and 100 µm. Materials and Methods. Eighteen milled lithium disilicate microdiscs (IPS e.max CAD, Ivoclar Vivadent) were divided into three groups (n = 6) according to their digital die spacer settings: group A = 20 µm, group B = 40 µm, and group C = 100 µm. Six randomly selected sound maxillary premolars received three microdiscs each. Each microdisc was 1 mm in diameter and 1 mm in height. The buccal surfaces of the premolars were prepared with a 0.5 mm depth in enamel. After cementation, the specimens were thermocycled for 2,500 cycles between 5 and 55°C. Microshear bond strength testing was performed using a universal testing machine until bonding failure. Failure modes were evaluated using a stereomicroscope. Statistical analyses included one-way ANOVA, Tukey’s post hoc test, and chi-square test with a 5% alpha error and 80% study power. Results. The mean microshear bond strength values were calculated in MPa for group A = 31.91 ± 12.41, group B = 29.58 ± 5.03, and group C = 13.85 ± 4.12. One-way ANOVA (p≤0.05) showed a statistically significant difference in microshear bond strength among the three groups. Tukey’s post hoc test showed significant differences between groups A and C (p=0.004) and between groups B and C (p=0.011). The failure modes were presented as cohesive, adhesive, and mixed failures. Chi-square test indicated that the failure mode distribution was not significantly different among the three groups (p=0.970). Conclusion. Higher digital die spacer settings decrease the microshear bond strength of CAD/CAM lithium disilicate veneers.